Feminist Consumerism Discourse in Dove Advertisements on Dove US YouTube Channel - Hermilawanda; Ela Martisa (ELITE: Journal of English Language and Literature, 2023)
The objective of this research is to find out how the feminist consumerism discourse described in “Dove” beauty in terms of gender identity, fashion, beauty standards and feminine beauty ideology by Talbot (2020). Feminist consumerism discourse is an ideology that forms a person or group carry out the process of using or consuming goods produced in a sustainable manner based only on desires, not needs. This research used descriptive qualitative method. The source of data in this research is Dove advertisements was taken from the Dove US YouTube channel. Data collection was done by downloading, watching, transcribing, selecting and coding based on Talbot’s theory. Data analysis cam carried out by presenting data, describing the context and situation, interpreting the data, concluding the results of data analysis. The data for this research are 11 feminist consumerism discourse data in Dove advertisements to support analytical process that the researcher is conducting. The researcher found that several elements of the feminist consumerism discourse that can be seen in the Dove advertisements video are in four aspects, such as gendered identity, fashion, beauty standards and feminine beauty ideology. From the several aspects above, the feminist consumerism discourse is found in Dove advertisements and there are also persuasive elements.